Cannabis sativa e a regulamentação pela ANVISA: um estudo sob a ótica jurídica - Epifânio, Felipe de Lira (Universidade Federal Rural do Semi-Árido, 2019)
Through a deductive research carried out in the main repositories of theses and dissertations of the country, through the bibliographic method, the present article aims to analyze the situation of patients in Brazil who opt for alternative health treatments with the use of cannabis sativa. It addresses the legal precedent of exclusion of unlawfulness of the cultivation of cannabis in the sole paragraph of art. 2 of Law 11.343/06, due to the inertia of ANVISA in its regulation. It analyzes the actions of the Judiciary in allowing the use and cultivation of cannabis for medicinal purposes, confronting this judicial activity with the constitutional Principle of Separation of Powers. Initially, it studies the issue of marijuana cultivation in Brazil through a historical-legal approach up to the current legislation, analyzing the main paradigm’s shifts in the relevant legislation and problematizing the lack of an objective criterion in the Drug Law on the characterization of the marijuana’s portage for consumption or for drug trafficking. In the second part of the research, it makes an approach of ANVISA's cannabis regulation as a holder of Police Power, since the change of marijuana from a banned list of drugs, allowing the importation of medication composed of cannabis, to the current situation of the discussion of the permission of its cultivation. Finally, it addresses whether there is interference by the Judiciary in the public policies of the State, analyzing the change of position of this Power in the actual configuration of a Democratic State of Law whose purpose is to guarantee the Fundamental Rights of persons, including those who depend on cannabis for a better quality of life and health
Artigo Acadêmico
Keywords: Cannabis; Cultivo; ANVISA; Poder judiciário; Separação dos poderes; Direitos fundamentais; Cannabis; Cultivation; ANVISA; Judiciary power; Separation of powers; Fundamental rights; CIENCIAS SOCIAIS APLICADAS::DIREITO